Effect of a Single Simulated 500 m Saturation Dive on Lung Function - Lian, Ningfang; Wang, Sijiao; Hu, Lijuan; Xue, Liping; Gong, Ying; Li, Li; Yang, Yanjie; Zhu, Lei (Frontiers in Physiology, 2022)
Background Whether deep saturation diving causes injury to lung function remains controversial and the mechanism is unclear. The present study aimed to evaluate the effects of a 500 m simulated single saturation dive on lung function. Methods A retrospective study was performed in 9 professional divers finished a single simulated 500-meter saturation dive in June, 2021. Pulmonary function parameters were measured and compared before and on 3 days after the dive. Results Nine professional divers with median age (36±7) years were enrolled. Three days after the dive, the parameters related to expiratory flow (forced expiratory volume in 1 second (FEV1) /forced vital capacity (FVC)) were decreased; the parameters related to small airway function (forced expiratory flow at 50% , 75% of FVC exhaled and forced mid-expiratory flow) were decreased compared with those before the dive (both P<0.05). Additionally, after the dive, the parameters related to pulmonary diffusion function were decreased compared with those before the dive (both P<0.05). The parameters related to lung volume (residual volume, vital capacity and total lung volume) and those related to respiratory exertion (peak expiratory flow and forced expiratory flow at 75% of FVC exhaled) were not significantly different between after and before the dive. Two divers with small airway dysfunction before the dive had obstructive ventilatory dysfunction after the dive. Additionally, mild obstructive ventilatory dysfunction in three divers before the dive became severe after the dive. After a bronchial dilation test, five divers showed improvement of FEV1, which ranged from 0.10 to 0.55 L. Chest radiographs and echocardiography of all divers were normal after diving. Conclusions 500 m simulated saturation diving induces a decrease in small airway function and diffusion function. This injury may be associated with small airway and diffusion membrane lesions.